Performance of capillary ceiling cooling panel on ceiling surface temperature and indoor thermal environment. Issue 6 (July 2020) - Xie, Dong; Wang, Chenhua; Yu, Chuck Wah; Wang, Yun; Wang, Hanqing
A new experimental methodology is presented to show the effect of water supply temperature, mass flow rate and thermal load distribution on the radiant ceiling capacity and thermal comfort conditions. Computerized fluid dynamics simulated vertical temperatures and velocities profiles were validated by a comparison with experimental results and the difference was within 10%. Uniform surface temperature distribution was achieved in a 45.6 m 3 test room installed with capillary ceiling radiant cooling panels by an increase in water temperature and air supply velocity. When the ventilation system was turned off, the mean ceiling surface temperature rose from 16.9 ± 0.4°C to 21.5 ± 0.3°C with a rise in the inlet water temperature to 20.1°C. The temperature difference between the head and ankle of an occupant was 2.0°C, which complies with the Chinese standard, GB/T 18049-2017. At a height of 1–1.5 m, the maximum temperature fluctuation was 2°C in the horizontal direction. When the ventilation system was turned on, with the air supply temperature and velocity at 19.8°C and 1.11 m s −1, the ceiling surface temperature was increased by 0.5°C. The indoor air temperature has a positive correlation with the air supply temperature and internal heat load but a negative correlation with air supply velocity.